Solve the following IVP by power series method
xy′′ + y′ + 2y = 0, y(1) = 2,y′(1) = 4.
Solution
New variable t = x-1 => x = t+1 and IVP is (t+1)y′′ + y′ + 2y = 0, y(0) = 2,y′(0) = 4.
Let
"y\\left(t\\right)=\\sum_{n=0}^{\\infty}{a_nt^n}"
"\\frac{dy}{dt}=\\sum_{n=1}^{\\infty}{na_nt^{n-1}}=\\sum_{n=0}^{\\infty}{\\left(n+1\\right)a_{n+1}t^n}"
"\\frac{d^2y}{dt^2}=\\sum_{n=0}^{\\infty}{n\\left(n+1\\right)a_{n+1}t^{n-1}}=\\sum_{n=0}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}t^n}"
Substitution into equation:
"\\left(t+1\\right)\\sum_{n=0}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}t^n}+\\sum_{n=0}^{\\infty}{\\left(n+1\\right)a_{n+1}t^n}+2\\sum_{n=0}^{\\infty}{a_nt^n}=0"
"\\sum_{n=0}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}t^n}+\\sum_{n=1}^{\\infty}{\\left(n+1\\right)na_{n+1}t^n}+\\sum_{n=0}^{\\infty}{\\left(n+1\\right)a_{n+1}t^n}+2\\sum_{n=0}^{\\infty}{a_nt^n}=0"
"2a_2+a_1+2a_0+\\sum_{n=1}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}t^n}+\\sum_{n=1}^{\\infty}{\\left(n+1\\right)^2a_{n+1}t^n}+2\\sum_{n=1}^{\\infty}{a_nt^n}=0"
Coefficients near tn are equal to zero.
n=0: 2a2 +a1 + 2a0=0 => a2 = -a1 /2 - a0
n>0: (n+1)(n+2)an+2+(n+1)2an+1+2an=0 => an+2 =-(n+1)an+1/(n+2)-2an/[(n+1) (n+2)]
From initial values for t: y(0) = 2,y′(0) = 4 => a0 = 2, a1 = 4
Therefore for recurrent formula an+2 =-(n+1)an+1/(n+2)-2an/[(n+1) (n+2)] with a0 = 2, a1 = 4 solution is
"y\\left(x\\right)=2+4\\left(x-1\\right)\\ +\\sum_{n=0}^{\\infty}{a_{n+2}\\left(x-1\\right)^{n+2}}"
Comments
Leave a comment